Optimal redistributive taxation and provision of public input goods in an economy with outsourcing and unemployment - Thomas Aronsson; Erkki Koskela (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper concerns optimal redistributive income taxation and provision of a public input good in a two-type model with a minimum wage policy implemented for the low-ability type, where firms may use some of their resources for outsourcing by locating part of the production process abroad. Our results show that the incentive to relax the self-selection constraint and the incentive to increase employment among the low-skilled reinforce each other in terms of marginal income taxation. In addition, the appearance of equilibrium unemployment also provides an incentive for the government to directly tax outsourcing. Without a direct instrument for taxing outsourcing, the government may reduce the amount of resources spent on outsourcing by increased provision of the public input good, which is desirable in the sense that reduced outsourcing contributes to less wage inequality and increased employment.
Keywords: H21; H25; J31; J62; 330; Outsourcing; optimal nonlinear taxation; public goods; unemployment; Optimale Besteuerung; Körperschaftsteuer; Outsourcing; Mindestlohn; Öffentliches Gut; Theorie